Determinants of Capital Structure in Energy Sector Companies Listed on the Indonesia Stock Exchange - Niati, Sukur; Sartika, Dewi (International Journal of Finance Research, 2024)
Capital structure is the balance between long-term debt and company capital. The source of capital itself can be obtained from debt sources and shareholder capital. which is also owned by the investor so that through a combination of these sources of funds, namely through debt and company capital, it can increase company profits. This study aims to determine the effect of return on assets, growth opportunity, sales growth, and asset structure on capital structure in energy sector companies listed on the Indonesia Stock Exchange in 2021-2023. This research uses a descriptive method with a quantitative approach. The population observed in this study were all energy sector companies listed on the Indonesia Stock Exchange, totaling 87 companies. The sample selection method in this study was determined by the purpose sampling method. The number of samples taken in this study were 20 companies. The results showed that the variable return on assets has no significant effect on capital structure, growth opportunity has a significant negative effect on capital structure, sales growth has a significant positive effect on capital structure, and asset structure has no significant effect on capital structure. This research implies that it is expected to provide input as a consideration for investors in making investments. In addition, this research is expected to contribute and refer to further research